Pengembangan Strategi Promosi Berbasis Media Sosial Digital pada Permata Laundry - Cuandra, Fendy; Kho, Chalvin (Pakis Journal Institute, 2026)
Permata Laundry is a laundry service micro, small, and medium enterprise (MSME) located in Batam City that faces increasing business competition due to the rapid growth of similar service providers. One of the main challenges encountered is the limited utilization of digital media for promotion and service delivery, which affects market reach and business visibility. This Community Service Program (PKM) aims to develop a digital media-based promotional strategy to enhance brand awareness, promotional effectiveness, and service efficiency at Permata Laundry. The method applied in this activity involves primary data collection through interviews and direct observation of business operations. Based on the analysis results, several outputs were designed and implemented, including the creation and optimization of a Google Maps business profile, the management of Instagram and TikTok social media accounts as promotional tools, and the implementation of an online ordering system using Google Forms integrated with QR Codes. The results indicate that the application of digital marketing strategies improves access to business information, customer interaction, and service efficiency. Therefore, digital-based promotional development has a positive impact on strengthening competitiveness and ensuring the sustainability of Permata Laundry in the digital era.